PENGARUH INTERVENSI RELAKSASI HIPNOSIS MODIFIKASI LIMA JARI TERHADAP TINGKAT KEPATUHAN MINUM OBAT PADA PASIEN DIABETES MELLITUS - Purwaningsih, Yustina; Hartanto, Agung Eko; Hendrawati, Gandes Widya (Universitas Sultan Ageng Tirtayasa, 2025)
Diabetes mellitus is a chronic disease that requires treatment over a long period of time. Compliance with taking medication is key in lowering blood sugar levels. The problem of non-compliance with taking medication is a problem that often arises in diabetes patients and causes complications. This study aims to determine the effect of Five Finger Modification Hypnosis Relaxation on the level of compliance with taking medication in DM patients. The research method uses true experimental research with pre and post test designs carried out on 1 control group and 1 intervention group. The population is diabetes mellitus patients in Sukosari village, Kec. Kauman District Ponorogo numbered 50 people, and the sample used was 35 people. Five finger modified hypnosis relaxation intervention was carried out in the intervention group and deep breathing relaxation and health education in the control group. analyzed using the Wilcoxon formula, and the P Volume results were 0.000 < 0.05, meaning that there was an influence of the five finger modified hypnosis relaxation intervention on the level of adherence to taking medication for diabetes mellitus in Sukosari Village, Kec. Kauman, Kab. Ponorogo. The conclusion is that deep breathing modification hypnotic relaxation can increase patient compliance in taking medication.